Defining a spectrum of metals biosorbed by Paenibacillus castaneae with respect to heavy metal contamination in Gauteng - Chinhoga, Nokuthula (My University, 2016)
Paenibacillus castaneae isolated from acid mine decant (Gauteng, South Africa) was previously shown to tolerate high concentrations of lead (Pb). The ability of the bacterium to tolerate/resist other heavy metals is probable and suggests a role for P. castaneae as a biosorbent for their removal from contaminated wastewaters. The current study aimed at determining whether the bacterium is also resistant to other common metal contaminants specifically, zinc (Zn) and nickel (Ni), found in South African wastewaters for biosorption by P. castaneae. Additionally, the influence of the external factors pH and competing cations on the uptake of these metals by the bacterium was evaluated. Specific rates of metal uptake (Q) were calculated indirectly from quantifying (by spectroscopy) the residual ion concentrations post exposure to 3 mM metal after various treatments. P. castaneae was found to tolerate Zn but showed vulnerability towards Ni. In a binary metal system, the bacterium showed a preferential metal uptake in the order Zn>>Co> Mn with a highest Q of 26 mg Zn/g biosorbent biomass recorded in the presence of Mn at pH 7. On the contrary, in a multimetal complex solution, the order of preference shifted to Co>>Zn with no absorption of Mn at the same pH. The results indicate that both pH and the presence of cations have an effect on the uptake of Zn by P. castaneae that could favour or inhibit its biosorption. The present study confirms the ability of P. castaneae to remove additional metals such as Zn, Mn and Co. These findings further suggest the potential of P. castaneae as a biosorbent for greener clean-up strategies of contaminated water facilities around Gauteng in the way of bioremediation. Keywords: P. castaneae, biosorption, specific metal uptake, zinc, lead, nickel
A research project submitted to the Faculty of Sciences, University of the Witwatersrand, in partial fulfilment of the requirements for the degree of Master of Science in Environmental Sciences (Coursework and Research Report). Johannesburg, 2016.
Keywords: Heavy metals--Environmental aspects; Sewage--Purification--Heavy metals removal; Sewage--Purification--Biological treatment